Prominent careers and Irish screen policy - Barton, Ruth; Murphy, Denis (Irish Journal of Arts Management and Cultural Policy, 2022)
Drawing on recent empirical research, we examine career construction among prominent Irish film and television drama workers. Our emphasis is on gender; state patronage; the role of networks; and the necessity to supplement incomes, all of which are observed to impact on building and maintaining screen industry careers. We locate our research within international studies of careers in the screen industries and locally within Irish studies, where the research emphasis has been on gender, notably female, equality. By identifying the key stages in career construction in the screen industries, we suggest how future policy interventions might be staged so as to intervene earlier in the career cycle. We draw on Clive Nwonka’s (2021) distinction between empowering interventions and transformative policies to distinguish between proposals that generally improve the career opportunities of those currently underrepresented in the screen industries and those that specifically implement policies around hiring.